Review papperProblems of differentiation of carpal tunnel syndrome and C6 and C7 radiculopathy - Gasik, Robert (Reumatologia/Rheumatology, 2007)
Differential diagnosis of carpal tunnel syndrome (CTS) and cervical spine radiculopathy is often based only on the case history and additional examination showing compression position of the nerve (ultrasonography), spinal roots (MRI) or anatomical tunnels through which nerve roots and nerves pass (X-ray, ultrasonography, CT). It may be a reason for wrong diagnosis in a group of patients with diffuse degenerative changes. In practice, the fundamental importance in evaluation of the nerve damage position is played by clinical examination which describes functional disorders of the nerve and indicates the position of its damage. In doubtful cases, electrodiagnostic examination eliminates any doubts.